Knowledge of Dental Students from Croatia, Slovenia, and Bosnia and Herzegovina about Dental Care of Oncology Patients - Iva Pedic; Livia Cigic; Danijela Kalibovic Govorko; Katarina Vodanovic; Ruzica Bandic; Robert Glavinic; Ivana Medvedec Mikic (MDPI AG, 2021)
The central role of the dentist in the treatment of oncology patients is to care for the patient's oral cavity before, during, and after radio/chemotherapy. The aim of this research was to determine the knowledge of dental students from five universities in three neighboring countries, Croatia (Split, Rijeka, and Zagreb), Bosnia and Herzegovina (Sarajevo), and Slovenia (Ljubljana), about oncology patients' dental care. A total of 140 students in their fourth, fifth, and sixth year of dental medicine studies participated in this research. A questionnaire with 36 specific questions was designed for this research and included questions about dental care of oncologic patients before, during, and after the oncology therapy. Most students are familiar with the incidence and most common type of head and neck tumors, while knowledge about tumor treatment and the side-effects of radiation therapy and/or chemotherapy is weak. Students did not show satisfactory knowledge about osteoradionecrosis, which is the most serious side-effect of radiotherapy; therefore, the emphasis on additional education should be greatest in this area. Teaching staff should be aware of lack of student knowledge and try to offer more information and practice in providing dental care for oncology patients.